SafeWalk App, mobile application in health for people living in motor disabilities. (May 2019) - Osorio, E A; Osorio, J D; García, D A
Abstract: The research had the objective of develop a mobile application in health for people with motor disabilities oriented to be multiplatform and will allow integrate different accessibility functionalities. The exploratory method was used to aproach reality and as instrument, information search was carried out in government sources, main mass media of the country, observation in public places and semi-structured interviews to health area professionals. With that information was possible identify the need of this population in term of mobility issues, either because of its near or far enviroment. The application will gather information of the places available to serve this population and will be used to accessibility to their interest places. Users will be able to part of a community of people with similar conditions, interact with them and share information. Also they will have the possibility of communicate with tutors that can provide various kinds of help and contact them through a button available across the interfaces of the applications. It will generate information that will can be rated by users to estimate if the registered places are really accessibles and have good rating from those who have already been there.